The conventional protocol vs. a protocol including illumination with a fabric‐based biophotonic device (the Phosistos protocol) in photodynamic therapy for actinic keratosis: a randomized, controlled, noninferiority clinical study. (1st August 2019) - Mordon, S.; Vignion‐Dewalle, A.S.; Abi‐Rached, H.; Thecua, E.; Lecomte, F.; Vicentini, C.; Deleporte, P.; Béhal, H.; Kerob, D.; Hommel, T.; Duhamel, A.; Szeimies, R.M.; et al.
Summary: Background: Topical photodynamic therapy (PDT) using methyl aminolaevulinate is a noninvasive treatment option suitable to treat clinical and subclinical actinic keratosis (AK) over a large area (field cancerization). The most widely used, conventional protocol in Europe includes illumination with a red‐light lamp. This illumination commonly causes pain, and patients often cannot complete the treatment. Objectives: The aims of this paper are twofold. The first aim is to introduce a novel protocol, the Phosistos protocol (P‐PDT), which includes illumination with a fabric‐based biophotonic device. The second and major aim is to assess the noninferiority, in terms of efficacy for PDT of AK, of P‐PDT compared with the conventional protocol (C‐PDT). Methods: A randomized, controlled, multicentre, intraindividual clinical study was conducted. Forty‐six patients with grade I–II AK of the forehead and scalp were treated with P‐PDT on one area (280 AK lesions) and with C‐PDT on the contralateral area (280 AK lesions). The primary end point was the lesion complete response (CR) rate at 3 months, with an absolute noninferiority margin of −10%. Secondary end points included pain scores, incidence of adverse effects and cosmetic outcome. Results: Three months following treatment, the lesion CR rate of P‐PDT was noninferior to that of C‐PDT (79·3% vs. 80·7%, respectively; absolute difference −1·6%; one‐sided 95% confidence interval −4·5% to infinity). The noninferiority of P‐PDT to C‐PDT in terms of the lesion CR rate remained at the 6‐month follow‐up (94·2% vs. 94·9%, respectively; absolute difference −0·6%; one‐sided 95% confidence interval −2·7% to infinity). Moreover, the pain score at the end of illumination was significantly lower for P‐PDT than for C‐PDT (mean ± SD 0·3 ± 0·6 vs. 7·4 ± 2·3; P < 0·001). Conclusions: P‐PDT is noninferior to C‐PDT in terms of efficacy for treating AK of the forehead and scalp and resulted in much lower pain scores and fewer adverse effects. What's already known about this topic? Topical photodynamic therapy using methyl aminolaevulinate is effective for treating actinic keratosis. In Europe, the conventional protocol involves illumination with a red‐light lamp. Unfortunately, pain is often experienced by patients undergoing this protocol. An alternative protocol that uses daylight illumination has recently been shown to be as effective as the conventional protocol while being nearly painless. However, this alternative protocol can be conducted only in suitable weather conditions. What does this study add? The Phosistos protocol is demonstrated to be as effective as the conventional protocol, nearly as painless as the daylight protocols and suitable year round for treatment of actinic keratosis. Abstract : Plain language summary available online Linked Comment: Gilaberte. Br J Dermatol 2020; 182 :11–12 .